Sulphonylurea usage in melioidosis is associated with severe disease and suppressed immune response. - Xiang Liu; Geraldine Foo; Wan Peng Lim; Sharada Ravikumar; Siew Hoon Sim; Mar Soe Win; Jessamine Geraldine Goh; Joan Hui Juan Lim; Ying Hui Ng; Dale Fisher; Chin Meng Khoo; Gladys Tan; et al. (Public Library of Science (PLoS), 2014)
BACKGROUND: Melioidosis is a problem in the developing tropical regions of Southeast Asia and Northern Australia where the the Gram negative saprophytic bacillus Burkholderia pseudomallei is endemic with the risk of fulminant septicaemia. While diabetes mellitus is a well-established risk factor for melioidiosis, little is known if specific hypoglycemic agents may differentially influence the susceptibility and clinical course of infection with B. pseudomallei (Bp). METHODOLOGY/PRINCIPAL FINDINGS: In this cohort study, patients with pre-existing diabetes and melioidosis were retrospectively studied. OUTCOME MEASURES: mortality, length of stay and development of complications (namely hypotension, intubation, renal failure and septicaemia) were studied in relation to prior diabetic treatment regimen. Peripheral blood mononuclear cells (PBMC) from diabetic patients and healthy PBMC primed with metformin, glyburide and insulin were stimulated with purified Bp antigens in vitro. Immune response and specific immune pathway mediators were studied to relate to the clinical findings mechanistically. Of 74 subjects, 44 (57.9%) had sulphonylurea-containing diabetic regimens. Patient receiving sulphonylureas had more severe septic complications (47.7% versus 16.7% p = 0.006), in particular, hypotension requiring intropes (p = 0.005). There was also a trend towards increased mortality in sulphonylurea-users (15.9% versus 3.3% p = 0.08). In-vitro, glyburide suppressed inflammatory cytokine production in a dose-dependent manner. An effect of the drug was the induction of IL-1R-associated kinase-M at the level of mRNA transcription. CONCLUSION/SIGNIFICANCE: Sulphonylurea treatment results in suppression of host inflammatory response and may put patients at higher risk for adverse outcomes in melioidosis.